A 68HC11-based digital thermometer - Siti Daniah Binti Salleh (2023)
This thesis describes the development of digital thermometer using 68HC11 microcontroller. The development of a microcontroller based product required the development of the software (program) and the hardware (electronic circuit). This project used the 68HC11 analog to digital converter. To measure the temperature, an integrated circuit sensor is used. The sensor chosen is LM35. This device gives an output voltage which is directly proportional to the temperature in Celsius. Seven segment LED display is used to display the temperature. beside hardware application, the software programming using 68HC11 assembly code is also mentioned in this thesis. This thesis also described the process of making Printed Circuit Board for the transducer circuit.